Investigation on the impact of transport exhaust emissions on the air - Baltrenas, Pranas; Vaitiekūnas, Petras; Mincevič, Irena (Journal of Environmental Engineering and Landscape Management, 2004)
The investigation carried out has revealed that in Vievis settlement and near the highway Vilnius ‐ Kaunas the highest concentrations of pollutants are emitted during morning and afternoon rush‐hours when motor transport traffic is the heaviest. Extremely high amounts of emitted aerosol particles were recorded 1–2 m away from the driving part, and 4–6 m away the amounts of aerosol particles sharply go down. CO gas concentrations caused by passing motor transport were also analysed. It has been set that the concentrations of CO and aerosol particles depend directly on motor transport traffic intensity. CO concentration goes evenly down receding from the driving part. In most cases maximum permitted concentration of CO was recorded. Automobilių išmetamų dujų poveikio atmosferai tyrimai Santrauka. Atlikus tyrimus Vievyje ir šalia esančioje automagistralėje Vilnius – Kaunas, nustatyta, kad daugiausia autotransporto teršalų išmetama rytinio ir vakarinio piko valandomis, kai eismo intensyvumas didžiausias. Ypač dideli išmetamų aerozolių dalelių kiekiai 1–2 m atstumu nuo važiuojamosios kelio dalies, o už 4–6 m staigiai sumažėja. Ištirta dėl pravažiuojančio autotransporto srautų susikaupusių CO dujų koncentracijos. Nustatyta, kad CO ir aerozolių dalelių koncentracijos tiesiogiai priklauso nuo autotransporto eismo intensyvumo. CO koncentracija tolygiai mažėja didėjant atstumui nuo kelio važiuojamosios dalies. Daugeliu atvejų CO (DLK) koncentracijos viršija didžiausias leistinąsias. Reikšminiai žodžiai: aplinka, atmosferos oro tarša, mobilieji teršimo šaltiniai, autotransportas. First Published Online: 14 Oct 2010